2018
DOI: 10.3390/rs10050697
|View full text |Cite
|
Sign up to set email alerts
|

Updating Absolute Radiometric Characteristics for KOMPSAT-3 and KOMPSAT-3A Multispectral Imaging Sensors Using Well-Characterized Pseudo-Invariant Tarps and Microtops II

Abstract: Radiometric calibration of satellite imaging sensors should be performed periodically to account for the effect of sensor degradation in the space environment on image accuracy. In this study, we performed vicarious radiometric calibrations (relying on in situ data) of multispectral imaging sensors on the Korea multi-purpose satellite-3 and -3A (KOMPSAT-3 and -3A) to adjust the existing radiometric conversion coefficients according to time delay integration (TDI) adjustments and sensor degradation over time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…6SV shows higher simulation accuracy than MODTRAN, RT3 and SHARM with less than 1% error under several atmospheric condition scenarios. Due to the high accuracy of 6SV, it is used in radiometric calibration, retrieval of AOD, and surface albedo studies, as well as for atmospheric correction (Zhang et al 2016;Wu et al 2017;Yeom et al 2018).…”
Section: S Rtmmentioning
confidence: 99%
See 1 more Smart Citation
“…6SV shows higher simulation accuracy than MODTRAN, RT3 and SHARM with less than 1% error under several atmospheric condition scenarios. Due to the high accuracy of 6SV, it is used in radiometric calibration, retrieval of AOD, and surface albedo studies, as well as for atmospheric correction (Zhang et al 2016;Wu et al 2017;Yeom et al 2018).…”
Section: S Rtmmentioning
confidence: 99%
“…It is not limited to a specific region or satellite sensor because it inputs the atmospheric conditions, geometry information, and sensor characteristics of areas where the atmospheric correction is to be performed. In addition, the RTM method is known to be accurate for simulating atmospheric effects in comparison with empirical line method (ELM) and improved dark-object subtraction (IDOS) (Zhou et al 2011); thus, it is used in various fields, as well as in atmospheric correction of satellite imagery (Zhao et al 2001;Liang et al 2012;Zhang et al 2016;Wu et al 2017;Yeom et al 2018). However, the RTM method has a disadvantage in that it takes a long time to perform atmospheric correction over a wide area, such as that of satellite images, because the calculation process is complex and the processing times are long.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental area is Seoul, which mainly contains built-up areas and forests. KOMPSAT-3 and KOMPSAT-3A have the same spectral response functions and practical spectral ranges as the bands that are affected by atmospheric constituents and the surface, where the main difference between them is only the spatial resolution [53]. Therefore, the experiment is performed by resampling KOMPSAT-3 at 2.2 m, which is the same resolution as KOMPSAT-3A, and the size of the images is set to 2000 × 1500 pixels.…”
Section: Additional Datasetmentioning
confidence: 99%
“…Shin et al [17] conducted a comparative study with both results of the TOA reflectance calculation using KOMPSAT-3A and Landsat 8 OLI images in the test area and reported that the quality of the KOMPSAT-3A images was consistently maintained. In a pilot study on the calibration of KOMPSAT-3/3A images, Yeom et al [18] performed calculations of TOA reflectance using the second simulation of the satellite signal in the solar spectrum (6S) algorithm, an important radiated transport model, and analyzed the absolute radiometric characteristics of KOMPSAT-3/3A. Ahn et al [19] produced atmospherically corrected images of Landsat or Sentinel-2 images and used them to propose an adjustment factor for KOMPSAT-3 for TOA reflectance.…”
Section: Introductionmentioning
confidence: 99%